2021
DOI: 10.1002/adsc.202100674
|View full text |Cite
|
Sign up to set email alerts
|

Radical Promoted Synthesis of Furoquinolines via Anomalous Dakin‐Type Reaction

Abstract: A radical promoted approach for the selective synthesis of furo[3,2‐b]quinolines and benzylidene‐1,3‐dihydrofuro[3,4‐b]quinolines have been achieved from 2‐alkynyl quinoline‐3‐carbaldehydes by fine‐tuning of base and oxidant in good yields. In the presence of an oxidant, the reaction afforded the 5‐endo‐dig cyclized furoquinolines by decarbonylative intramolecular cyclization via a Dakin‐type reaction; however, in the absence of oxidant, 5‐exo‐dig cyclized products were obtained selectively through reductive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recently, several reactions, involving the use of strong bases in DMF, DMSO, and DMAc solvents, were proposed to proceed via an electron-transfer mechanism. In these reactions, deprotonation of the solvent produces the corresponding anion which was transformed to the carbamoyl radical (from DMF), dimsyl radical (from DMSO), or dimethylcarbamoyl radical (from DMAc) by a subsequent single-electron transfer to the solvent molecule . Furthermore, electron transferred from the carbamoyl, dimsyl, and dimethylcarbamoyl anion to various species such as aryl iodides, aryl methyl sulfones, and benzil derivatives had resulted in the formation of the corresponding radicals . Sliwka et al showed that the formation of long-lived-radical species by the addition of small quantities of strong bases to DMF and DMSO at room temperature …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several reactions, involving the use of strong bases in DMF, DMSO, and DMAc solvents, were proposed to proceed via an electron-transfer mechanism. In these reactions, deprotonation of the solvent produces the corresponding anion which was transformed to the carbamoyl radical (from DMF), dimsyl radical (from DMSO), or dimethylcarbamoyl radical (from DMAc) by a subsequent single-electron transfer to the solvent molecule . Furthermore, electron transferred from the carbamoyl, dimsyl, and dimethylcarbamoyl anion to various species such as aryl iodides, aryl methyl sulfones, and benzil derivatives had resulted in the formation of the corresponding radicals . Sliwka et al showed that the formation of long-lived-radical species by the addition of small quantities of strong bases to DMF and DMSO at room temperature …”
mentioning
confidence: 99%
“… 16 Furthermore, electron transferred from the carbamoyl, dimsyl, and dimethylcarbamoyl anion to various species such as aryl iodides, aryl methyl sulfones, and benzil derivatives had resulted in the formation of the corresponding radicals. 17 Sliwka et al showed that the formation of long-lived-radical species by the addition of small quantities of strong bases to DMF and DMSO at room temperature. 18 …”
mentioning
confidence: 99%